Positive end-expiratory pressure induced changes in airway driving pressure in mechanically ventilated COVID-19 Acute Respiratory Distress Syndrome patients - Cruz, Mônica Rodrigues da (2023)
Ethics approval and consent to participate: Protocols were approved by institutional review boards of the National Institute of Infections Diseases (CAAE 31050420.8.2001.5262), Pedro Ernesto University Hospital (CAAE 31050420.8.1001.5259), Brazilian clinical trials (RBR-2z3f7k).